2015
DOI: 10.1042/bj20150059
|View full text |Cite
|
Sign up to set email alerts
|

Solution NMR characterization of chemokine CXCL8/IL-8 monomer and dimer binding to glycosaminoglycans: structural plasticity mediates differential binding interactions

Abstract: Structural plasticity plays a major role in determining differential binding of CXCL8 monomer and dimer to glycosaminoglycans (GAGs) and that dimer is the high-affinity GAG ligand. We propose that these properties play important roles in orchestrating in vivo chemokine-mediated neutrophil function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
107
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(118 citation statements)
references
References 66 publications
(71 reference statements)
10
107
0
Order By: Relevance
“…This suggests that chemical shift changes from direct and indirect interactions are of opposite sign and similar magnitude and, therefore, cancel out. We made similar observations earlier for CXCL8, where lysines known to be involved in GAG binding from functional studies showed minimal backbone chemical shift changes (26).…”
Section: Characterization Of Gag-hcxcl1supporting
confidence: 66%
See 4 more Smart Citations
“…This suggests that chemical shift changes from direct and indirect interactions are of opposite sign and similar magnitude and, therefore, cancel out. We made similar observations earlier for CXCL8, where lysines known to be involved in GAG binding from functional studies showed minimal backbone chemical shift changes (26).…”
Section: Characterization Of Gag-hcxcl1supporting
confidence: 66%
“…Interestingly, CXCL5, CXCL8, and KC actually have an acidic residue at the third ␤-strand position. NMR studies of CXCL8 and KC show evidence of binding only to the ␣-domain (26,32). In addition, only CXCL1, CXCL2, and CXCL3 have a basic residue at the end of the first ␤-strand.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations